2015
DOI: 10.1097/nmd.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

Paranoid Delusional Disorder Follows Social Anxiety Disorder in a Long-Term Case Series

Abstract: Social anxiety disorder (SAD) patients may have self-referential ideas and share other cognitive processes with paranoid delusional disorder (PDD) patients. From an evolutionary perspective, SAD may derive from biologically instinctive social hierarchy ranking, thus causing an assumption of inferior social rank, and thus prompting concerns about mistreatment from those of perceived higher rank. This naturalistic longitudinal study followed four patients with initial SAD and later onset of PDD. These four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Evolutionary accounts of paranoia have been proposed before (1,2) but have largely focused on paranoia as over-sensitive or misplaced social threat perception (1). Given that misperceiving social threat would seem to be a serious problem for forming and maintaining productive social relationships, this article focuses on an evolutionary account of why paranoid thinking is such a common human characteristic and why paranoia can become intense and disabling after many forms of social, psychological and neurological difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary accounts of paranoia have been proposed before (1,2) but have largely focused on paranoia as over-sensitive or misplaced social threat perception (1). Given that misperceiving social threat would seem to be a serious problem for forming and maintaining productive social relationships, this article focuses on an evolutionary account of why paranoid thinking is such a common human characteristic and why paranoia can become intense and disabling after many forms of social, psychological and neurological difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…In this article we argue that paranoia involves all of these socio-cognitive abilities and that the human ability for paranoid thinking evolved in response to these social selection pressures. Evolutionary accounts of paranoia have been proposed before 11,12 but have not fully accounted for the full phenomenological complexity of paranoia, nor shown how such a perspective has the potential to explain variation in paranoia both across contexts and over development. We explore why paranoid thinking is such a common human characteristic and why paranoia can become intense and disabling after many forms of social, psychological and neurological difficulties.…”
mentioning
confidence: 99%
“…49 Veras et al reported four cases of patients first diagnosed with social anxiety disorder (SAD), followed, after a period of time, by a diagnosis of DD. 50 This shows that SAD, in some cases, can be a prodromal form of DD.…”
Section: Primary and Secondary Preventive Strategies On An Individual...mentioning
confidence: 92%
“…Social anxiety disorder (SAD) SAD can lead to delusions. 50 CBT for SAD. 50 Panic attacks Anticipatory anxiety and panic can lead to DD.…”
Section: Anxiety Comorbiditiesmentioning
confidence: 99%